Intravenous Lipid Emulsion for treating Tramadol-Induced Seizures: Surprising but Worth Considering for Future Studies; a Letter to Editor - Megarbane, Bruno; Gouda, Ahmed S. (Archives of Academic Emergency Medicine, 2022)
We read with interest the article reporting benefits of intravenous lipid emulsion (ILE) in preventing tramadol-induced in-hospital seizures in poisoned patients (1). We would first like to congratulate the authors for this impressive randomized investigation. However, we wish to comment on their findings. The main presumed mechanism of action for ILE in acutely poisoned patients, named “lipid sink”, is limiting tissue distribution of lipophilic drugs potentially causing toxicity. Based on an in vitro model, ILE’s ability to sequester a drug was shown to parallel its octanol-water partition coefficient (2), defined as the ratio of its concentration in a water-saturated octanolic phase to its concentration in an octanol-saturated aqueous phase and usually expressed as “LogP”. Prediction of drug binding with ILE was additionally improved by combining its LogP with volume of distribution (VD), together accounting for ~88% of ILE-attributed variation in its serum concentration decrease (2).